PENGARUH CORPORATE IMAGE, CUSTOMER RELATIONSHIP MARKETING DAN LAYANAN FINTECH TERHADAP LOYALITAS NASABAH (Studi Kasus Pada Bank Syariah Indonesia KC. Kota Malang) - Hoiriyah Ali; Nur Diana; M Cholid Mawardi (El-Aswaq: Islamic Economics and Finance Journal, 2022)
This study aimed to determine the effect of Corporate Image, CustomerRelationship Marketing, and Fintech Services on Customer Loyalty (Case study atBank Syariah Indonesia KC. Malang City). This type of research is quantitativeresearch. The object of research used is all customers of Bank BSI KC. MalangCity, Sutoyo. This study took a sample of 100 respondents. The samplingtechnique used is probability sampling. The data used in this study are primarydata obtained from distributing questionnaires. The data obtained were thenprocessed with SPSS version 16.0, and the data analysis used in this research wasmultiple linear regression analysis. The results of this study indicate that theindependent variable, namely Corporate Image (X1), has a partial negative effecton Customer Loyalty (Y). Variable Customer Relationship Marketing (X2) Has apositive and significant impact on Customer Loyalty (Y). And the FinancialTechnology variable (X3) has a positive and significant effect on CustomerLoyalty (Y). In contrast, the variables Corporate Image (X1), CustomerRelationship Marketing (X2), and Fintech Services (X3) have a positive andsignificant effect simultaneously on Customer Loyalty.